The Effect of Incentives and Leadership Styles on Creative Performance - Sariyatul Ilyana; Mahfud Sholihin (Journal of Indonesian Economy and Business (JIEB), 2021)
Introduction/Main Objectives: This study investigates whether the type of incentives offered and leadership styles interact to affect creative performance. Background Problems: Creativity is highly needed by companies to survive in a volatile business environment. Prior research found that management control systems and the leadership style were able to stimulate creativity. It is still unclear which type of incentives and leadership styles are able to stimulate creativity. Therefore, this research proposes a research question, what kind of management control systems and leadership style can improve creative performance? Novelty: This research focuses on comparing monetary and non-monetary incentives, based on competition, to produce the most creative ideas, but empirical studies into the context of creativity are still limited. Furthermore, this study investigates two different leadership styles and it sheds light on the fact that the leadership styles needed in a creative environment differ from those styles used in a non-creative environment. Research Methods: This study was conducted using a 2x2 between subject experimental design with two incentive treatments (tournament and recognition) and two leadership style treatments (directive and empowering). Finding/Results: Consistent with Lourenco (2016), monetary incentives (including tournaments) and non-monetary incentives (recognition) are substitutive. Furthermore, the empowering leadership style leads to a greater creative performance than the directive style does. The results indicate that, in the condition of a tournament incentive, empowering leadership is able to produce a higher creative performance than directive leadership can. Conclusion: There is no significantly difference between the effect of monetary incentives and non-monetary incentives on creative performance. This study’s result is consistent with the situational leadership theory, certain types of leadership are appropriate for certain environmental conditions. For improved creative performance, employees need to be empowered because they need the authority and freedom to develop ideas. This study provides knowledge about the impact of incentives and leadership styles on creative performance. Furthermore, this study provides practical knowledge for companies on how to improve creativity in the work environment by using certain incentives and leadership styles.